"Dental Cements Based on Acid Degradable Glasses/Ion Leachable Glasses" – A Review. Issue 2 (2nd April 2016) - Nagaraja Upadhya, P.; Ginjupalli, Kishore; Srinivasan, K. K.; Adhikari, A. V.; Satapathy, L. N.
ABSTRACT: Glass ionomer cement (GIC) is one of the most versatile cements used in dentistry. It came into existence in the late 1960s mainly to overcome the drawbacks of its predecessor material 'dental silicate cements'. Since then, it has undergone several improvisations and modifications to meet the requirements of various dental applications. The GIC consists of basic glass powder and acidic polyacids, which sets by an acid-base reaction between the components. The glass component of GIC plays a major role in the clinical performance of the material. It provides the source of ions for the cement formation, controls the strength, imparts translucency and provides a therapeutic benefit by releasing fluoride. Glass structure-reactivity-processing are the three main aspects to be considered when designing the glass compositions for cement formation. From the conventional calcium fluoroaluminosilicate glass to the current aluminium free glasses, GIC has received significant attention in the recent past to further extend its applications in various fields. The purpose of this article is to provide relevant discussion on the scientific development of the GIC from the glass science and technology point of view. GRAPHICAL ABSTRACT: